Building Herb Culture in Tourist Destination to Develop Health Tourism: Evidence From Central Java Indonesia - Sugiarti, Rara; Pujiasmanto, Bambang; Marwanti, Sri (Universitas Sebelas Maret, 2022)
This study highlights how far medicinal plants found in many areas of Klaten Central Java are utilized to build herb culture and support health tourism, i.e. tourism which provides travellers with good habits of consuming healthy food and drinks while in the destination. This descriptive research applied qualitative approach and employed several data collection techniques which include site observation, interview, focus group discussion, and document study. Data were analysed using interactive and thematic analysis technique. Results show that most eating places including restaurants and food stalls in tourist destinations do not provide traditional drinks made of medicinal plants such as ginger, tamarind, turmeric, curcuma zanthorrhiza (temulawak), and kaempferia galanga (kencur). Tourism stakeholders have not yet realized the potentials to build herbs culture where the locals provide traditional drinks made of medicinal plants and the tourists consume them in tourist destinations to perform health tourism.